Karakteristik Efisiensi Air Cooler dengan Penambahan Sponge di Kabin Kapal Papua Jaya Karya - Yohanes R. Purnomo; Immawan Insani (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2023)
The direct evaporative cooling system is a very simple method used to cool the air. This research aims to determine the characteristics of air coolers by comparing air coolers that have not been modified with air coolers that have been modified. Modifications to the air cooler by adding a sponge placed in front of the honey comb cooling pad with dimensions p = 30 cm, l = 25 cm, t = 1.5 cm. Tests were carried out using an air cooler by comparing the working fluids used in the form of water and ice water and using 3 different air velocities. The characteristics of the air cooler in this study show that the comparison of the air cooler with the modification of adding sponge is better than without modification. The efficiency value during testing shows that at low speed with fluid conditions in the form of ice water in the air cooler with the modification of adding sponge, it has the highest value, namely η = 97.4%. This is caused by air contact with water on the cooling pad at low speed for longer than at higher speeds, which causes heat absorption in the air to be more efficient.